The organization of cognitive representation of group-specific tactics in soccer - Lex, H. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Scientific protocols describing tactical performance usually investigate indicators (e.g., running distances, maximum running speed etc.) derived from post-hoc video analyzes (Garganta, 2009). However, the results of a novel scientific approach showed that more experienced soccer players possess a functional cognitive re-presentation of team-specific tactics in soccer. More experienced soccer players end up with faster decisions, because of their functional representation structure allowing to coordinate their gaze behavior aligned to tactical needs (Lex, Essig, Knoblauch, & Schack, 2015). In soccer, performance is not only determined by team-specific tactics. Thus, the present study investigates the cognitive representation of group-specific tactics in soccer. Methods: The present study investigated whether cognitive representations are established for group-specific tactics in defense (i.e. defense triangle, four-man backfield defense, golden zone defense) and offense (i.e., give and go pass, overlap, two players crossing) with regard to players expertise. Participants (N = 45) made similarity judgments of 2 x 9 match situations displayed on a tactic board (i.e., 144 decisions) in a successive splitting procedure regarding the required tactical behavior. The de-cisions informed about the proximity between the match situations, and formed the basis for an unweighted average cluster analysis (p = .01,dcrit = 4.48) complemented by an invariance measure testing structural homogeneity ( crit = .68). Results: Experienced soccer players possess, in contrast to less experienced players ( = 0.0), a structural invariant cognitive representation for offense and defense tactics identical with the representation structure of experienced coaches ( = 1.0) and players from the Bundesliga ( = 1.0). We found no differences between players specialized for defense and offense tactics. However, players with a coaching license showed as well a functional cognitive representation of group-specific tactics ( = 1.0). Discussion: This innovative experimental approach measuring individual cognitive representations of group-specific tactics in soccer reveals a well-integrated network of single match situations that each corresponds to functional meaningful group-specific tactics based on soccer specific playing experiences. The cognitive representations of group-specific tactics form an individual profile of each player, which allows to refer to tactical decision making on the pitch.